The Crisis of the Long 1850s and Regime Change in the Ionian State and the Kingdom of Greece - Gekas, Sakis (The Historical Review/La Revue Historique, 2013)
The overthrow of King Othon in 1862 and the decolonization of the Ionian Islands led to the unification of the Ionian State with the Kingdom of Greece. This article argues that the multifaceted crisis of the long 1850s (1847-1862) created a crisis of legitimacy for both the British Protectorate and the Othonian regime. The change of regime represents a case where an economic, social and political crisis set in motion a process of democratization and not the rise of an authoritarian regime (as in the 1930s). The argument balances socio-economic structuralist factors with the contingency of political action that determined the union of the two states; this regime change was the optimal and favoured solution and the way out of the legitimacy crisis for all actors involved.